Endothelial-Specific Overexpression of Caveolin-1 Accelerates Atherosclerosis in Apolipoprotein E-Deficient Mice - Fernández-Hernando, Carlos (American Society for Investigative Pathology, 2010)
Caveolin-1 (Cav-1) is the major structural protein essential to the formation of the caveolae in endothelial cells. Genetic ablation of Cav-1 on an apolipoprotein E knockout background inhibits the progression of atherosclerosis, whereas re-expression of Cav-1 in the endothelium promotes lesion expansion. Although Cav-1-null mice are useful to delineate the importance of caveolae in atherosclerosis, there are additional problems that are difficult to dissect because loss of Cav-1 abolishes both the caveolae organelle as well as the Cav-1-mediated signaling pathways. To study how Cav-1 influences the progression of atherosclerosis in mice with caveolae, we generated a transgenic mouse that overexpresses Cav-1 in the endothelial cells in an apolipoprotein E-deficient background. We found that endothelial-specific overexpression of Cav-1 enhanced the progression of atherosclerosis in mice. Mechanistically, overexpression of Cav-1 reduced endothelial cell proliferation, migration, and nitric oxide production in vitro and increased expression of vascular cell adhesion molecule-1 in vivo.